How Can Tourism Achieve Long-Term Resilience After Crises And Disruptions? Crisis Management Model - Hendhana, Sandra; Gede Sri Darma; Luh Putu Mahyuni; Agus Fredy Maradona (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2024)
The tourism industry has faced numerous crises and disruptions around the world. The global travel and tourism industry is currently suffering substantial economic losses as a result of a health-related crisis, specifically the COVID-19 pandemic. As a result, tourism-related organizations have a growing interest in crisis management, including disaster management and risk management. The present study examines the tourism industry's strategies for effectively managing crises and disruptions, focusing on fostering long-term resilience. This study examines more than just the disruption caused by health-related crises. To get insight into the adoption of crisis management and resilience strategies within the tourism industry, a comprehensive analysis was conducted on 43 articles spanning a period of ten years (2012-2022). This study uses the Systematic Literature Review method. This study presents a novel theme conceptual framework that can guide future research endeavors on resilience and crisis management within the tourism sector. The study identified three primary themes on the resilience of the tourist sector in effectively managing and responding to crises and disruptions. The first is adaptive responses, the second is innovations, and the transformation model is the third theme. The results and discussion sections will explain each theme in more detail.